Ca²⁺ does not affect the binding properties of ITSN1 EH domains - Morderer, D.Ye.; Rymarenko, O.V.; Skrypkina, I.Ya.; Rynditch, A.V. (Вiopolymers and Cell, 2014)
ITSN1 is an endocytic scaffold protein implicated in synaptic functioning. Ca²⁺ is known to be important for endo- cytosis in both pre- and post-synaptic terminals. ITSN1 contains two EH (Eps15 homology) domains which possess putative Ca²⁺-binding EF-hand motifs. Aim. To test the effect of Ca²⁺ on the EH domain binding properties. Methods. His-tag pulldown, Western blotting. Results. Addition of 1.5 mM Ca²⁺ does not affect the binding of the ITSN1 EH domains to the C-terminal fragment of the endocytic protein Epsin 1. Conclusions. The data obtained indicate that Ca²⁺ has no effect on the binding properties of the ITSN1 EH domains. ITSN1 – адаптерний білок ендоцитозу, залучений до функціонування синапсів. Відомо, що іони Ca²⁺ є важливими для ендоцитозу у пре- та постсинаптичних закінченнях. ITSN1 має два ЕН-домени, гомологічних Eps15, які містять передбачені Ca²⁺-зв’язувальні мотиви EF-hand. Мета. Перевірити ефект іонів Ca²⁺ на зв’язувальні властивості доменів ЕН. Методи. Преципітація білків, злитих з His-тагом, Вестерн-блот-гібридизація. Результати. Показано, що додавання 1,5 мМ Ca²⁺ не впливає на зв’язування ЕН-доменами ITSN1 С-кінцевого фрагмента білка ендоцитозу Епсину 1. Висновки. Отримані дані свідчать про відсутність ефекту іонів Ca²⁺ на зв’язувальні властивості ЕН-доменів ITSN1. ITSN1 – адапторный белок эндоцитоза, вовлеченный в функционирование синапсов. Известно, что ионы Ca²⁺ важны для эндоцитоза в пре- и постсинаптических окончаниях. ITSN1 имеет два ЕН-домена, гомологичных Eps15, которые содержат предсказанные Ca²⁺-связывающие мотивы EF-hand. Цель. Проверить эффект ионов Ca²⁺ на связывающие свойства доменов ЕН. Методы. Преципитация белков, слитых с His-тагом, Вестерн-блот- гибридизация. Результаты. Показано, что добавление 1,5 мМ Ca²⁺ не влияет на связывание ЕН-доменами ITSN1 С-концевого фрагмента белка эндоцитоза Эпсина 1. Выводы. Полученные данные свидетельствуют об отсутствии эффекта ионов Ca²⁺+ на связывающие свойства ЕН-доменов ITSN1.